Strategy Map dan Rancangan Balanced Scorecard PT. DPI - A Fakhri Arifyanto (BISMA (Bisnis dan Manajemen), 2018)
This research aims to compile and designing Strategy Map and Balanced Scorecard on PT. DPI in order to achieve the objective of becoming an international organization or world class company.  According to David P. Norton which had been quoted by Mathews (2007), Balanced Scorecard is precise methodologies to develop measurement which is capable to describe the organizations strategy.  Development of Strategy Map is the key to design effective Balanced Scorecard. The analysis result stated that the Strategy Map of PT. DPI could be compiled by virtue of the strategic issues in the corporate level, meanwhile for the Balanced Scorecard design consists of four perspectives in which financial perspective to improve the ROI of strategic objective by increasing revenue from existing product and new product.  Customer perspective, with the strategic objective of customer satisfaction, increased market share by retaining existing customers and add new customers.  Internal Business Process Perspective, with a strategic objective of developing superior products, innovative and sophisticated, improved customer relationship management.  Learning and Growth Perspective, with strategic objectives to improve the quality, professionalism of human resources DPI, to develop a conducive climate in DPI (improve DPI climate).